Factors that affecting stock prices in Malaysia / Nor Sharmimiey Ahmad And Norazifah Aziz - Ahmad, Nor Sharmimiey; Aziz, Norazifah (2014)
Stock is very important element of an economy because stock market plays a role in the growth of key sector of the economy. Stock is a one of the asset that can give profit and return to the investor. This paper investigate the factors that affecting prices of stock for 28 firms listed in the KLCI covering period from 2004 until 2014 by using interest rate, inflation rate, exchange rate and money supply as independent variables. For the data collected the analysis is made by using the STATA. The result shows that money supply has positive relationship with stock price and this variable have also significant relationship with stock price